Respuesta :

2x - 8y = 6

-2x + 2y = 7

Add the two equations together by combining like terms:

2x + -2x = 0

-8y + 2y = -6y

and 6 + 7 = 13

So when you combine the terms you end up having:

-6y = 13

Now solve for y by dividing each side by -6:

y = 13/-6

Rewrite by moving the negative sign in front of the fraction to get

y = -13/6

The answer is C.

Question :-

Solve for y in the two equations below using substitution.

  • 2x - 8y = 6
  • -2x + 2y = 7

____________________

Solution :-

Given Information :-

  • Equation 1 ➢ 2x - 8y = 6
  • Equation 2 ➢ -2x + 2y = 7

To Find :-

  • Solve for y in the two equations.

Calculation :-

Equation 1 ➢ 2x - 8y = 6

Equation 2 ➢ -2x + 2y = 7

Adding both equations together, by combining similar terms, We get,

  • 2x + -2x = 0
  • -8y + 2y = -6y
  • 6 + 7 = 13

When we combine the terms, We get,

⇒ -6y = 13

Now, solving for y, by divide Right Hand Side & Left Hand Side by -6, We get,

⇒ y = [tex] \sf \frac{13}{-6} [/tex]

⇒ y = [tex] \sf \frac{-13}{6} [/tex]

∴ The value of y is [tex] \bf \frac{-13}{6} [/tex]

____________________

Final Answer :-

The value of y is [tex] \bf \frac{-13}{6} [/tex]

Hence, Option C. [tex] \bf \frac{-13}{6} [/tex] is correct answer.

____________________